Transitions to an Ecological Age. - Metzner, Ralph (Trumpeter: Journal of Ecosophy)
The article discusses the emergence of the transition to an Ecological Age. According to the author, the global environmental crisis offers both a challenge and an opportunity for all the disciplines to reformulate some of the fundamental questions and issues in every area of human knowledge and inquiry. A growing chorus of voices acknowledges that the fundamental roots of the environmental disaster lie in the attitudes, values, perceptions, and basic worldview that humans have come to hold. To this basis, theologian Thomas Berry proposes that if a cultural transition does take place, humans will then be able to find their rightful place as participants in the integral interdependent community of life.